Formulation and evaluation of naproxen sodium orodispersible tablets – A sublimation technique - Jeevanandham, S; Dhachinamoorthi, D; Sekhar, K B Chandra; Muthukumaran, M; Sriram, N; Joysaruby, J (Asian Journal of Pharmaceutics (AJP), 2014)
The rationale of this investigation was to develop fast dissolving tablets of naproxen sodium using camphor as a subliming agent. Orodispersible tablets of naproxen sodium were prepared by the wet granulation technique using camphor as a subliming agent and sodium starch glycolate together with crosscarmellose sodium as superdisintegrants. Camphor was sublimed from the granules by exposing the granules to vacuum. The porous granules were then compressed into tablets. Alternatively, tablets were first prepared and later exposed to vacuum.The formulations were evaluated for weight variation, hardness, friability, drug content, wetting time, and in vitro dissolution. All the formulations showed low weight variation with dispersion time less than 55 s and rapid in vitro dissolution. Sublimation of camphor from tablets resulted in superior tablets as compared with the tablets prepared from granules that were exposed to vacuum. The results revealed that the tablets containing the subliming agent had a good dissolution profile.The drug content of all the formulations was within the acceptable limits of the United States Pharmacopoeia XXVII. The optimized formulation showed good release profile with maximum drug being released at all time intervals. It was concluded that fast dissolving tablets with improved naproxen sodium dissolution could be prepared by sublimation of tablets containing a suitable subliming agent. This work helped in understanding the effect of formulation processing variables especially the subliming agent on the drug release profile.